Side‐effects of carbetocin to prevent postpartum hemorrhage: A systematic review and meta‐analysis of randomized controlled trials - Wen Ai; Yanfei Zeng; Yubo Ma; Li Liu; Dazhi Fan; Song Wu; Yinghui Zhang (Wiley, 2021)
Abstract Postpartum hemorrhage (PPH) increases the risk of maternal death worldwide. Heat‐stable carbetocin, a long‐acting oxytocin analog, is a newer uterotonic agent. Clinicians do not fully understand its side‐effects, particularly the unanticipated side‐effects. The aim of this study is to investigate the side‐effects of carbetocin to PPH. The Cochrane Library, Web of Science, PubMed, Elsevier ScienceDirect, Embase, and ClinicalTrials.gov were searched from the inception to September 2020. Randomized controlled trials (RCTs) that considered pregnant women who received carbetocin before delivery and provided at least one adverse event were included. Statistical analysis included random or fixed‐effect meta‐analyses using relative risk. Stratified analyses and sensitivity analyses were also performed. Begger's and Egger's test and funnel plots were used to assess the publication bias. Seventeen RCTs involving 32,702 women were included, and all these studies ranked as medium‐ to high‐quality. Twenty‐four side‐effects were reported. The use of carbetocin had a lower risk of vomiting in intravenously (0.53, 0.30 to 0.93) and cesarean birth (0.51, 0.32 to 0.81) women, and had a slightly higher risk of diarrhea (8.00, 1.02 to 62.79) compared with oxytocin intervention. No significant difference was found among other side‐effects. Evidence from our systematic review and meta‐analysis of 17 RCTs suggested that the risk of vomiting decreased with carbetocin use in the prevention of PPH after delivery.